Radioactivity in the Kuwait marine environment — Baseline measurements and review. Issue 2 (30th November 2015) - Uddin, S.; Aba, A.; Fowler, S.W.; Behbehani, M.; Ismaeel, A.; Al-Shammari, H.; Alboloushi, A.; Mietelski, J.W.; Al-Ghadban, A.; Al-Ghunaim, A.; Khabbaz, A.; Alboloushi, O.
Abstract: The Arabian Gulf region is moving towards a nuclear energy option with the first nuclear power plant now operational in Bushehr, Iran, and others soon to be constructed in Abu Dhabi and Saudi Arabia. Radiological safety is becoming a prime concern in the region. This study compiles available data and presents recent radionuclide data for the northern Gulf waters, considered as pre-nuclear which will be a valuable dataset for future monitoring work in this region. Radionuclide monitoring in the marine environment is a matter of prime concern for Kuwait, and an assessment of the potential impact of radionuclides requires the establishment and regular updating of baseline levels of artificial and natural radionuclides in various environmental compartments. Here we present baseline measurements for 210 Po, 210 Pb, 137 Cs, 90 Sr, and 3 H in Kuwait waters. The seawater concentration of 3 H, 210 Po, 210 Pb, 137 Cs, and 90 Sr vary between 130–146, 0.48–0.68, 0.75–0.89, 1.25–1.38 and 0.57–0.78 mBq L − 1, respectively. The 40 K concentration in seawater varies between 8.9–9.3 Bq L − 1 . The concentration of 40 K, total 210 Pb, 137 Cs, 90 Sr, 226 Ra, 228 Ra, 238 U, 235 U, 234 U, 239 + 240 Pu and 238 Pu were determined in sediments and range, respectively, between 353–445, 23.6–44.3, 1.0–3.1, 4.8–5.29, 17.3–20.5, 15–16.4, 28.7–31.4, 1.26–1.30, 29.7–30.0, 0.045–0.21 and 0.028–0.03 Bq kg − 1 dry weight. Since, radionuclides are concentrated in marine biota, a large number of marine biota samples covering several trophic levels, from microalgae to sharks, were analyzed. The whole fish concentration of 40 K, 226 Ra, 224 Ra, 228 Ra, 137 Cs, 210 Po and 90 Sr range between 230–447, 0.7–7.3, < 0.5–6.6, < 0.5–15.80, < 0.17, 0.88–4.26 and 1.86–5.34 Bq kg − 1 dry weight, respectively. 210 Po was found to be highly concentrated in several marine organisms with the highest 210 Po concentration found in Marica marmorata (193.5–215.6 Bq kg − 1 dry weight). 210 Po in most dissected fish samples shows increasing concentrations in the following order: edible tissue, gills, digestive system, liver and fecal matter. Fish fecal pellets had 210 Po concentrations several orders of magnitude higher than the seawater, fish muscle, and the fishes' ingested food. The high 210 Po concentration in fish fecal matter, suggest that the bulk of 210 Po content in fish was eventually excreted back into the environment as fecal pellets. In most fish high concentrations were noted in liver, with the highest 210 Po concentration recorded in shark liver (126.2–141.5 Bq kg − 1 wet). Moreover, 210 Po concentration in the soft tissue of molluscs (10.36–215.60 Bq kg − 1 dry weight) was far higher than that in fish muscle (0.05–7.49 Bq kg − 1 wet weight). A seasonal drop in 210 Po concentration in seawater was observed to vary with the abundance of phytoplankton and macroalgae due possibly to biological dilution. 137 Cs concentration in all the fish sampled was below the detection limit, and the concentration in seawater was also low; hence such low levels provide an opportunity to use this radionuclide as an indicator for any future radiocesium releases in this region. Highlights: Here we present baseline measurements for 210 Po, 210 Pb, 137 Cs, 90 Sr, and 3 H in Kuwait waters. The seawater concentration of 3 H, 210 Po, 210 Pb, 137 Cs, and 90 Sr is similar to other oceans. Biota samples covering several trophic levels, from microalgae to sharks, were analyzed. Fish fecal pellets had 210 Po concentrations several orders of magnitude higher than the seawater. The highest 210 Po concentration measured in biota from this region was in shark liver.